OUTCOMES COMPARISON AFTER SMALL INCISION LENTICULE EXTRACTION (SMILE) AND FEMTOSECOND-LASER ASSISTED IN SITU KERATOMILEUSIS (FS-LASIK) IN LOW-MODERATE MYOPIA PATIENTS: Oral Presentation - Observational Study - Resident - ANDREAS LUKITA HALIM; Budiman; Mayang Rini; Andrew M. H. Knoch; Emmy Dwi Sugiarti; Ludwig Melino Tjokrovonco (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Uncorrected myopia is the leading cause of visual impairment globally. It can be corrected by refractive surgeries, such as Small Incision Lenticule Extraction (SMILE) and Femtosecond Laser- Assisted In Situ Keratomileusis (FS-LASIK). SMILE technique is less-invasive than FS-LASIK, characterized by all-in-one femtosecond laser and flapless procedure. Correction of low-moderate myopia requires a special concern because even slight decreased in visual quality may be noticed by the patients and affect their satisfaction. The purpose of this study to compare the refractive outcomes after SMILE and FS-LASIK in low-moderate myopia patients. Methods : This is a prospective analytical observational study that was conducted in a tertiary hospital in Indonesia. Four refractive outcome parameters (predictability, efficacy, safety, and stability) were assessed at 1 day, 1 week, and 1 month postoperatively. Results : SMILE was performed on 22 eyes with spherical equivalent (SE) -3.60±1.07 D and FS-LASIK on 20 eyes with SE -2.91±1.53 D. At 1 month, the predictability as the proportion of eyes within SE ±0.50 D were 95.5% in SMILE and 80% in FS-LASIK (p=0.174), the efficacy as the proportion of eyes achieving uncorrected distant visual acuity (UDVA) ≥20/20 were 63.6% in SMILE and 35% in FS- LASIK (p= 0.064), the stability as the proportion of eyes experiencing SE change >0.50 D were 4.5% in SMILE and 5% in FS-LASIK (p=1.000). No eyes from both groups had corrected distant visual acuity (CDVA) loss of ≥2 lines (p=1.000). Conclusion : SMILE and FS-LASIK were both predictable, effective, safe, and stable for low-moderate myopia patients.